Markus Hinterhaüser, pianist and more (ORF, 2007)
The pianist Markus Hinterhäuser in portrait. The Austrian Markus Hinterhäuser, extraordinary pianist and Concert Director at the Salzburger Festspiele, is impossible to categorize. He has established himself as an allround-artist and creative lateral thinker -- you won't find any of the well-known, common composers at one of his increasingly rare concerts. One is much more likely to come across Morton Feldman, John Cage, Giacinto Scelsi, or Galina Ustvolskaya. A very intimate portrait, showing this exceptionally talented man at work as well as his private sides following him to La Spezia, his birthplace in Italy